Metastatic Cervicomedullary Lesion in the Postpartum Period: A Case-Based Review of CNS Metastases in Pregnancy and Postpartum Period - Goyal, Sarvesh; Pandey, Kushagra; Kalappuraikkal, Arunath; Bora, Santanu Kumar; Narwal, Anubhav; Gupta, Deepak (Indian Journal of Neurosurgery, 2025)
Central nervous system (CNS) metastases in pregnancy are exceedingly rare but represent a complex and life-threatening condition requiring prompt diagnosis and a multidisciplinary approach. This report highlights a rare case of cervicomedullary junction metastasis in a postpartum patient, exploring diagnostic challenges and management strategies. A 32-year-old woman, postcesarean section, presented with progressive quadriparesis and dysphagia, weeks after delivery. Initial symptoms of neck pain during pregnancy resolved postpartum but rapidly worsened, leading to diagnostic uncertainty. Contrast-enhanced MRI revealed a cervicomedullary lesion. Given the rarity of cervicomedullary metastases and the overlapping presentation with pregnancy-related neurological conditions, there was a delay in identifying the underlying malignancy. CNS metastases in pregnancy are most commonly linked to breast cancer, melanoma, and gestational trophoblastic disease (GTD), with choriocarcinoma being particularly aggressive. However, nongestational metastases, such as in our case, are significantly underreported. Pregnancy-related physiological changes, including immune modulation and hormonal influences, may accelerate tumor progression, complicating the clinical picture. Our patient's presentation of quadriparesis and bulbar dysfunction was initially confused with other pregnancy-related conditions, highlighting the importance of maintaining a high index of suspicion for neurological compromise in pregnant and postpartum women. Early diagnostic imaging with contrast-enhanced MRI is critical for timely intervention. Management of CNS metastases in pregnancy poses unique challenges due to concerns regarding maternal and fetal health. Surgical decompression was performed for our patient due to rapid neurological decline. For surgically inaccessible lesions, stereotactic radiosurgery (SRS) offers a viable alternative, with minimal extracranial radiation exposure. Whole-brain radiotherapy (WBRT) and chemotherapy, while effective, are typically reserved for cases of multiple metastases or systemic disease. Obstetric considerations, such as timing of delivery, are also paramount, with early cesarean section often necessary in cases of severe neurological compromise. CNS metastases in pregnancy are rare but require rapid diagnosis and a tailored treatment approach. Early recognition of symptoms, timely imaging, and surgical intervention are essential to improving patient outcomes. Nongestational metastases remain underreported, and further research is needed to refine management guidelines, incorporating advanced imaging and molecular profiling. Our case underscores the importance of considering CNS metastasis in the differential diagnosis of postpartum patients with neurological symptoms, particularly in cases with cervicomedullary junction involvement.
Keywords: central nervous system metastases; cervicomedullary junction metastasis; postnatal neurological deficits